1998
DOI: 10.1016/s0092-8674(00)80897-1
|View full text |Cite
|
Sign up to set email alerts
|

Restricted and Regulated Overexpression Reveals Calcineurin as a Key Component in the Transition from Short-Term to Long-Term Memory

Abstract: To investigate the roles phosphatases play in hippocampal-dependent memory, we studied transgenic mice overexpressing a truncated form of calcineurin. These mice have normal short-term memory but defective long-term memory evident on both a spatial task and on a visual recognition task, providing genetic evidence for the role of the rodent hippocampus in spatial and nonspatial memory. The defect in long-term memory could be fully rescued by increasing the number of training trials, suggesting that the mice hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
183
1
6

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(194 citation statements)
references
References 46 publications
3
183
1
6
Order By: Relevance
“…PP2B/calcineurin has been reported to be important for mechanisms of synaptic plasticity such as long-term depression (LTD) (Mulkey et al, 1993;O'Dell and Kandel, 1994) and depotentiation (Zhuo et al, 1999). Furthermore, PP2B/ calcineurin has been shown to alter long-term potentiation (LTP) (Malleret et al, 2001;Winder et al, 1998;Mansuy et al, 1998). Thus, understanding mechanisms of PP2B/ calcineurin regulation could provide valuable insight into regulation of glutamatergic signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…PP2B/calcineurin has been reported to be important for mechanisms of synaptic plasticity such as long-term depression (LTD) (Mulkey et al, 1993;O'Dell and Kandel, 1994) and depotentiation (Zhuo et al, 1999). Furthermore, PP2B/ calcineurin has been shown to alter long-term potentiation (LTP) (Malleret et al, 2001;Winder et al, 1998;Mansuy et al, 1998). Thus, understanding mechanisms of PP2B/ calcineurin regulation could provide valuable insight into regulation of glutamatergic signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…We next explored whether the CaN-A-GABA A receptor complex formation is sufficient for the induction of LTD. We expressed the CaN catalytic domain, CaN-A␣, in the hippocampus of transgenic mice (CN98 mutant mice) (Mansuy et al, 1998;Winder et al, 1998). We affinity precipitated extracts from the CN98 mutant and control CA1 slices using GST-␣ 1 334 -420 , -␤ 2 327-451 , and -␥ 2S 317-442 .…”
Section: Overexpression Of Can-a Reduces Mgaba a R-ipscsmentioning
confidence: 99%
“…Behavioral experiments carried out in the laboratory of Eric Kandel demonstrated that long-term memory is lost after expression of a truncated dominant negative form of calcineurin in the hippocampus of trained mice. However, the ability to precisely remember the previously learned tasks can be completely restored after extinction of the dominant negative calcineurin (89). Readers interested in exploring further applications using second-generation mouse models in physiology are referred to several additional but more specialized reviews for cardiovascular disease (112), for neurobiology (88,159), for endocrinology/metabolism (117), and for cancer (60,63).…”
Section: Invited Reviewmentioning
confidence: 99%